Sirtuin 1 ameliorates defenestration in hepatic sinusoidal endothelial cells during liver fibrosis via inhibiting stress‐induced premature senescence. (1st February 2021) - Luo, Xiaoying; Bai, Yangqiu; He, Shuli; Sun, Suofeng; Jiang, Xiaoke; Yang, Zhiyu; Lu, Di; Wei, Peiru; Liang, Yuan; Peng, Cong; Wang, Yaru; Sheng, Ruli; et al.
Abstract: Objective: Premature senescence is related to progerin and involves in endothelial dysfunction and liver diseases. Activating sirtuin 1 (SIRT1) ameliorates liver fibrosis. However, the mechanisms of premature senescence in defenestration of hepatic sinusoidal endothelial cells (HSECs) and how SIRT1 affects HSECs fenestrae remain elusive. Methods: We employed the CCl4 ‐induced liver fibrogenesis rat models and cultured primary HSECs in vitro, administered with the SIRT1‐adenovirus vector, the activator of SIRT1 and knockdown NOX2. We measured the activity of senescence‐associated β‐galactosidase (SA‐β‐gal) in HSECs. Meanwhile, the protein expression of SIRT1, NOX2, progerin, Lamin A/C, Ac p53 K381 and total p53 was detected by Western blot, co‐immunoprecipitation and immunofluorescence. Results: In vivo, premature senescence was triggered by oxidative stress during CCl4 ‐induced HSECs defenestration and liver fibrogenesis, whereas overexpressing SIRT1 with adenovirus vector lessened premature senescence to relieve CCl4 ‐induced HSECs defenestration and liver fibrosis. In vitro, HSECs fenestrae disappeared, with emerging progerin‐associated premature senescence; these effects were aggravated by H2 O2 . Nevertheless, knockdown of NOX2, activation of SIRT1 with resveratrol and SIRT1‐adenovirus vector inhibited progerin‐associated premature senescence to maintain fenestrae through deacetylating p53. Furthermore, more Ac p53 K381 and progerin co‐localized with the abnormal accumulation of actin filament (F‐actin) in the nuclear envelope of H2 O2 ‐treated HSECs; in contrast, these effects were rescued by overexpressing SIRT1. Conclusion: SIRT1‐mediated deacetylation maintains HSECs fenestrae and attenuates liver fibrogenesis through inhibiting oxidative stress‐induced premature senescence. Abstract : SIRT1‐mediated deacetylation of p53 relieves NOX2‐dependent oxidative stress and inhibits progerin‐associated premature senescence to maintain fenestrae in HSECs.